Aerobic exercise improves spatial memory in a rat model of meningitis - Zaidah, Lailatuz; Soetrisno, Soetrisno; Purwanto, Bambang; Kristiyanto, Agus; Wasita, Brian; Widyaningsih, Vitri (Narra J, 2024)
Infections of the nervous system, such as acute bacterial meningitis, pose serious health problems that require immediate intervention. In experimental animals, exposure to lipopolysaccharide (LPS) is used to induce meningitis. Aside from drug intervention to reduce inflammation in meningitis, aerobic exercise helps to maintain the regulatory mechanisms of brain homeostasis through anti-inflammatory mechanisms. The aim of this study was to evaluate the effect of aerobic exercise on malondialdehyde (MDA), nuclear factor-kappa B (NF-κB), insulin-like growth factor 1 (IGF-1), endothelial nitric oxide synthase (eNOS), brain-derived neurotrophic factor (BDNF), apoptosis, and spatial memory. A four-week experimental study was conducted using 18 rats, which were randomly divided into three different groups (six rats per group): healthy rats as negative controls (non-meningitis), a treatment group treated with antibiotic treatment (meningitis group), and a third group (aerobic exercise group) treated with antibiotics and aerobic exercise following LPS-induced meningitis. Data were analyzed using a one-way analysis of variance (ANOVA) test, and the comparison between groups used the Bonferroni post-hoc test. The results showed that aerobic exercise significantly reduced MDA (p<0.001), NF-κB (p=0.035), and apoptosis (p=0.020) while increasing the serum levels of IGF-1 (p<0.001), eNOS (p=0.011), and BDNF (p=0.001) levels. Improvement in spatial memory was significant in the aerobic exercise group (p<0.001). This study suggested that aerobic exercise could be a promising adjunct therapy in meningitis management strategies, particularly due to its effect on improving spatial memory. Further clinical trials are needed to confirm these findings for clinical use.